Solve for h 28=4h+3(h+7)

Math
28=4h+3(h+7)
Rewrite the equation as 4h+3(h+7)=28.
4h+3(h+7)=28
Simplify 4h+3(h+7).
Tap for more steps…
Simplify each term.
Tap for more steps…
Apply the distributive property.
4h+3h+3⋅7=28
Multiply 3 by 7.
4h+3h+21=28
4h+3h+21=28
Add 4h and 3h.
7h+21=28
7h+21=28
Move all terms not containing h to the right side of the equation.
Tap for more steps…
Subtract 21 from both sides of the equation.
7h=28-21
Subtract 21 from 28.
7h=7
7h=7
Divide each term by 7 and simplify.
Tap for more steps…
Divide each term in 7h=7 by 7.
7h7=77
Cancel the common factor of 7.
Tap for more steps…
Cancel the common factor.
7h7=77
Divide h by 1.
h=77
h=77
Divide 7 by 7.
h=1
h=1
Solve for h 28=4h+3(h+7)

Meet the Team our Math Expers

Our Professionals

Robert Kristofer

Anna Frok

Magnus Flores

Lydia Fran

We are MathExperts

Solve all your Math Problems: https://elanyachtselection.com/

We can solve all your math problems
Scroll to top